2015
DOI: 10.1091/mbc.e14-11-1523
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic hGle1A regulates stress granules by modulation of translation

Abstract: Stress granules and translation are in dynamic equilibrium, but the mechanisms regulating them are not fully defined. Here we show isoform-specific roles for human Gle1: Gle1B functions in mRNA export, whereas, during stress, Gle1A coordinates translation and stress granule formation. This gives insight into how mRNA fate is controlled and has implications for human disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 79 publications
9
78
1
Order By: Relevance
“…At 37°C, both GFP-hGle1-IVS14-2A>C and GFP-hIPK1 exhibited cytoplasmic steady state localization, with no apparent localization at the nuclear envelope or nucleoplasm (Figure 1). The cytoplasmic distribution of GFP-hGle1-IVS14-2A>C with exclusion from the nucleus was indistinguishable from previously reported hGle1A localization (Kendirgi et al, 2003; Kaneb et al, 2015; Aditi et al, 2015), and had no similarity to hGle1B localization (Kendirgi et al, 2003; Folkmann et al, 2013). Interestingly, as previously observed for both hGle1A and hGle1B, GFP-hGle1-IVS14-2A>C was recruited to SGs upon heat shock at 45°C (Figure 1).…”
Section: Resultscontrasting
confidence: 71%
See 4 more Smart Citations
“…At 37°C, both GFP-hGle1-IVS14-2A>C and GFP-hIPK1 exhibited cytoplasmic steady state localization, with no apparent localization at the nuclear envelope or nucleoplasm (Figure 1). The cytoplasmic distribution of GFP-hGle1-IVS14-2A>C with exclusion from the nucleus was indistinguishable from previously reported hGle1A localization (Kendirgi et al, 2003; Kaneb et al, 2015; Aditi et al, 2015), and had no similarity to hGle1B localization (Kendirgi et al, 2003; Folkmann et al, 2013). Interestingly, as previously observed for both hGle1A and hGle1B, GFP-hGle1-IVS14-2A>C was recruited to SGs upon heat shock at 45°C (Figure 1).…”
Section: Resultscontrasting
confidence: 71%
“…Previously, we reported that hGle1 is a component of SGs and is required for SG assembly and disassembly (Aditi et al, 2015). Interestingly, hIPK1, the kinase required for producing hGle1’s cofactor IP 6 , also relocalizes to SGs upon stress (Brehm et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations